(untitled) (American Journal of Economics and Business Innovation, 2025)
The advancement of digital technology in the financial sector has changed operations, with developing economies witnessing a huge impact of the rapid advancement of digital technology in the financial sector. However, not much literature on the old and new realities of digital financial technology on the financial sector of developing economies exist. This study is conducted to provide an understanding of the old and new realities of digital technology advancements impacts on developing economies financial sectors. The study employs both qualitative and quantitative research methods. Five (N-5) commercial financial institutions in Ghana made up of 400 samples were selected, and bootstrapping was carried out, weighing every 400 cases (the critical value taken was t = 1.95 and a p-value <0.05) to guarantee the statistical weight of the SartPLS. The reliability of the indicators was assessed by the statistical significance of the standardized factorial loadings. The outer loadings were in the range of 0.40 to 0.60 should be excluded, and the evaluation should be higher than 0.70, indicating a compounded reliability increase. The compound reliability is the alternative to Cronbach’s alpha, and as a common rule, the score obtained should be expected to be higher than 0.70. The study results showed that government’s continuous dominance in the financial sector of developing economies remain strong. Also, leveraging digital technology would capacitate developing economies to take advantage of opportunities in the global financial market to achieve a guarantee sustainable financial sector growth and development.